ChemInform Abstract: Catalyst and Solvent‐Free Cyclopropanation of Electron‐Deficient Olefins with Cyclic Diazoamides for the Synthesis of Spiro[cyclopropane‐1, 3′‐indolin]‐2′‐one Derivatives. Issue 18 (May 2015) - Karthik, Govindaraju; Rajasekaran, Tamilselvan; Sridhar, B.; Reddy, B.V.Subba
Abstract The simple method provides the title products in high yield as mixtures of diastereomers.